Meshless Collocation Method for Inverse Source Identification Problems (Advances in Applied Mathematics and Mechanics, 2018)
A novel meshless scheme is proposed for inverse source identification problemsof Helmholtz-type equations. It is formulated by the non-singular general solutionsof the Helmholtz-type equations augmented with radial basis functions. Underthis meshless scheme, we can determine smooth source terms from partially accessibleboundary measurements with accurate results. Numerical examples are presented toverify validity and accuracy of the present scheme. It is demonstrated that the presentscheme is simple, accurate, stable and computationally efficient for inverse smoothsource identification problems.